The 5E instructional model in the meaningful learning of science and technology - Melgarejo, Teófilo Félix Valentín; Atanacio, Lilia Mariela Matos; Leandro, Aníbal Isaac Carbajal; Faustino, Liz Ketty Bernaldo; Rivarola, Marleni Mabel Cárdenas; López, José Rovino Alvarez; Chavez, Juana Toribia Gonzales (Frontiers in Education, 2024)
The primary objective of the study was to determine the influence of the 5E instructional model on the meaningful learning of Science and Technology in the students of the El Amauta Pedagogical Research and Innovation Laboratory, belonging to the province of Pasco - Perú. The methodological process responds to the quantitative approach, applied with a pre-experimental design to a sample of 22 students selected intentionally, to whom the instructional model was applied for the development of learning. The application of the instrument and the results obtained through the Wilcoxon test showed 0.008 < 0.05. Therefore, the 5E instructional model influences the achievement of Science and Technology learning of the students of the aforementioned educational institution.